GuttaFlow bioseal as monocone obturation technique in curved root canals: a scanning electron microscopy study / Musliana Mustaffa ... [et al.] - Mustaffa, Musliana; Ar Rahmah Nasri, Hajar; Kamarulzaman, Insyirah; Mohd Ibrahim, Mohamad Shafiq (Faculty of Applied Sciences, 2021)
The obturation quality of GuttaFlow Bioseal in curved root canals is not commonly investigated although there has been a current approach toward utilizing this material in extracted molars in recent years. This study assessed the obturated surface area, extrusion of root filling material beyond the apical foramen and duration of obturation procedure in curved root canals using monocone obturation technique. Access cavity was prepared in 20 human mandibular molars. Root canals with curvature of more than 10 as determined according to Schneider's method were included. Samples were prepared using Hyflex CM rotary files and divided into two groups (n=10): Group 1 [gutta-percha cone and GuttaFlow Bioseal] and Group 2 [gutta-percha cone and RoekoSeal Automix root canal sealer]. The duration of obturation procedure was recorded and obturation radiographs were taken. Samples were bisected and the mesial roots were sectioned horizontally to obtain 3 root segments; apical, middle and coronal. All resected roots were mounted on brass stubs, sputter-coated with thin platinum coating and observed under scanning electron microscope (SEM) at 70x magnification. The SEM images were transferred to the SketchAndCalc Area Calculator software. No statistically significant differences in the obturated surface area and extrusion of root filling material were observed between Group 1 and 2, irrespective of the status of root canal curvature. Duration for obturation in severe root canal curvatures between Group 1 and 2 were statistically significant. Obturated surface area and extrusion of root filling material were not affected by the root canal curvature, however duration for obturation using GuttaFlow Bioseal in severe root canal curvatures was slightly longer.